Compare Differences Between Different Bible Translations in the View of Globalization: Illustrated by the Case of "ψυχή" in the New Testament - Chang, Cheng-hao (Cultural and religious studies, 2017)
The purpose of Bible translation is to enable readers to fully understand what the Bible says in their own context. The different Bible translations use different translation principles, therefore, they show different translated results from each other. In general, translators will make translation choices between the "word-for-word translation" and "sense-for-sense translation". A good translation usually has two translation choices and the difference is just which kind of choice to use more. In addition to this, whether the same word can be translated consistently is also worthy of being discussed, especially in the case of a proper noun or vocabulary with special meaning. If a vocabulary with special meaning in the Bible is translated into different words, it is not only impossible to clarify the conceptual connection or logical relationship between certain words in the Bible, but also makes it possible for readers who read different Bible translations to have the different understanding of the vocabulary. Under the influence of globalization, Christian communication has become more frequent. After different readers read different Bible translations, the problem of inconsistent understanding of the same word or paragraph will be gradually revealed. This article uses the Greek word "ψυχή" to explore the above issues. "ψυχή" is a vocabulary with special meaning in the New Testament and it is mostly discussed in the anthropology of Christian theology. This article compares three English Bible translations and six Chinese Bible translations on the Greek word "ψυχή" and then finds that the Greek word "ψυχή was translated into multiple different words in a single Bible translation and in different Bible translations. This situation shows that the difference in translation may make the readers of different Bible translations have different understandings after reading.